Employees’ Self-Determination in Collegial Learning Situations at Work: A Comparative Study of a Finnish ICT Organization and a Central Hospital - Sara Keronen; Soila Lemmetty; Kaija Collin (Scandinavian Journal of Work and Organizational Psychology, 2023)
Expert work, seen as continuous learning and development, requires autonomy and responsibility at the individual level and collegiality and sharing of expertise at the team level. To have strong intrinsic motivation, employees must have the volition, ability, and interest to develop themselves and gain new knowledge. Enabling intrinsic motivation requires the self-determination to fulfill three basic psychological needs: autonomy, competence, and relatedness. However, self-determination not only relies on an individual’s own activity but is also influenced by the demands, obstacles, and affordances of the sociocultural context. Likewise, studies on learning in expert work in the field of adult education have shown that collegiality and social interaction are vital resources for learning. Therefore, this study explores employees’ self-determination in collegial learning situations in expert work in two contexts. A comparative qualitative research strategy and directed content analysis were utilized. The data consist of thematic interviews (N = 56) with employees from a Finnish central hospital and a Finnish information and communication technology organization. The findings show that self-determination is an essential part of collegial learning in modern expert work, thus providing the motivation behind learning. Social interaction can be seen as an enabler of employees’ sense of self-determination to be fulfilled in learning situations. The paper concludes with a discussion of the commonalities and differences in self-determination in collegial learning situations in these two expert work contexts. Finally, suggestions for future research are provided.